'Learning the "encynicals"': the Catholic Workers' College Dublin 1951-1965 - SEERY, AIDAN (My University, 2011)
The Catholic Workers? College founded in 1951 by the Society of Jesus (Jesuits) in Dublin remains an interesting case of Irish adult and trades union education as the College, society and education changed between the 1950s and 1990s. This paper presents a singular and personal description of the very early years of the College as a result of a life-history project with one of the authors (McKenna). This personal story is augmented by a sketch of the social-historical, ecclesiastical, and Jesuit-historical context that led to the establishment and considers some of the factors that influenced the early life and later direction of the College and its mission.
European Conference on Educational Research (ECER)
PRESENTED
Berlin
Keywords: workers' education; Jesuit colleges; Identities in Transformation